2005
DOI: 10.1002/masy.200551135
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Characterization of Polymer and Clay Platelet Orientation in Blown Films Based on Polypropylene‐Clay Nanocomposite

Abstract: The “tilted film” transmission infrared spectroscopy method was used to characterize the biaxial orientation in a set of blown films containing polypropylene (PP), layered silicate nano‐reinforcement, and two different compatibilizing agents based on maleic‐anhydride‐grafted PP. Both interactive spectral subtraction and peak fitting were used to determine trichroic ratios. The biaxial orientation of the polymer chains could be clearly quantified according to well‐established relationships for PP. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…These authors concluded that while the permeability decreased significantly, the amount of moisture absorbed remained mostly unchanged. Although they are outside the scope of this article, measurements of polymer and clay platelet orientation at the surface of the injected specimens by means of infrared spectroscopy in the attenuated total reflection mode have shown that the clay platelets are highly oriented parallel to the surface, in a manner similar to that observed for blown PP films [16]. This result suggests that, as discussed above, the barrier properties of our different nanocomposites during a subsequent exposure to water should be improved, by creating a maze-like tortuous path that should retard the progress of water molecules through the matrix resin.…”
Section: Resultsmentioning
confidence: 74%
“…These authors concluded that while the permeability decreased significantly, the amount of moisture absorbed remained mostly unchanged. Although they are outside the scope of this article, measurements of polymer and clay platelet orientation at the surface of the injected specimens by means of infrared spectroscopy in the attenuated total reflection mode have shown that the clay platelets are highly oriented parallel to the surface, in a manner similar to that observed for blown PP films [16]. This result suggests that, as discussed above, the barrier properties of our different nanocomposites during a subsequent exposure to water should be improved, by creating a maze-like tortuous path that should retard the progress of water molecules through the matrix resin.…”
Section: Resultsmentioning
confidence: 74%
“…In addition, the stretching vibrations of the basal oxygen bonds with silicon are at around 1117, 1050 and 1020 cm À1 [6]. As noted by Cole et al [7] the clay Si-O stretching bands are indeed complex. For the fit of the stretching vibrations two components for each of the peaks at 1050 and 1070 cm À1 were used.…”
Section: Introductionmentioning
confidence: 63%
“…This performance was achieved through a synergy of montmorillonite nanofillers and EVA-copolymer additive, that resulted in a general cohesive failure behavior. This resulted in peelable heat seals independent of sealing method (ranging from high pressure and 8 s dwell time, to low pressures and sub-second dwell times) over a very broad range of seal temperatures (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) • C range for the nanocomposites, instead of 2-5 • C for neat PE sealants, or 10 • C for PB-containing peelable sealants), as well as markedly independent of the seal substrate (on itself, on typical PE sealants and on HDPE). The origins and the mechanism of Figure 12.…”
Section: Discussionmentioning
confidence: 99%
“…Given the extensive use of polyethylene sealants worldwide, and the possible enhanced performance of polyethylene/clay nanocomposite films (which combine high gas barrier, optical transparency and improved thermomechanical properties [29][30][31][32][33][34][35]) it is very timely to study and tailor the heat-sealing performance of PE/clay nanocomposites, if their use in flexible packaging is to be proliferated. In general, fused PE seals are well established and are straightforward to realize and to manufacture.…”
Section: Introductionmentioning
confidence: 99%